DEFINITION OF PATIENTS GENETIC PREDISPOSITION TO INCREASED WEAR OF DENTAL HARD TISSUES - I.M. Tkachenko (Ukrainian Medical Stomatological Academy, 2015)
In literature the information about research issues that the morphology of the teeth mainly caused by hereditary factors and the process of dentinogenesis regulated by many genes is not found. In our view, the genetic defect level in laying the epithelial authority may be the main factors that determine genetic susceptibility of patients to high abrasion. Violation of the protein components further leads to a change in the conclusion mineral crystal lattice and thus to change or violation of the structure of enamel prisms. It is process we believe the main etiological factor of high abrasion. After the morphogenesis of dental hard tissue throughout life not updated their biocenose internal environment is maintained by the dental pulp, cellular cement, periodontal fibers and saliva. In the matrix of tooth enamel developing there are two types of proteases. Early enamelizyn protease (MMP-20), at the end of enamel formation protease kallikrein 4 (KLK4). Mutations in MMP20 and KLK4 which cause autosomal recessive imperfect of amelogenesis lead to clinical presentation of soft (for physical characteristics) porous enamel which is unable to withstand functional stress due to trace amounts of protein content. There was a monitoring of 170 patients under the supervision at experimental groups, of which those of the control group had no manifestations of increased abrasion of teeth and tooth rows were intact, and study groups, patients had a degree of wear of the teeth and in the third degree (according to the classification AN relatively Bushan high abrasion). Of all patients with high wearness and third-degree method chosen sample of 72 men for the study to detect the presence of polymorphisms of genes: 30 men, 42 women. The mutant selection (A) and "wild" (G) allele types KLK4 genes and MMP-20 was amplified using allele-specific polymerase chain reaction. Regarding alleles were selected genotypes with different types of displays mutations: GG, GA and AA in accordance with the dominant and recessive representation. Patients with genotype GG degree II met with a frequency of 74,8% (n = 28), GA and AA genotypes - with a frequency of 23,0% (n = 9) and 5,2% (n = 2), respectively. In 6 patients with III degree of abrasion of teeth increased frequency of genotypes KLK-4 gene was as follows: GG - 33,3% (n = 2), GA - 50% (n = 2) AA - 16,7% (n = 2 ). These data show that in the group with stage I high abrasion of teeth prevalent patients with "wild-type" genotype GG, and a group of III degree - patients with genotypes AA and GA. So, between the frequencies of genotypes GG and GA genotypes AA and gene KLK-4 data groups difference was found at the level of statistical significance (χ2 = 4,64; p = 0.031). In the study of gene MMP-20 G allele in patients with I and II degree of increased wear of the teeth met with a frequency of 92.6% and 83.3%, respectively, and allele A - 7.4% and 16.7%, respectively, which are not had a statistically significant difference. The results of the studies found no significant difference genotypes in the event of increased abrasion and second degrees of severity, which can be explained by various etiological factors noted by many authors in the study of the emergence of increased wear of teeth: this is where the terrain was born and lives of patients at increased wearness, living and working conditions, the presence of somatic diseases.